2015
DOI: 10.1007/s00421-015-3146-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen uptake and heart rate kinetics during dynamic upper and lower body exercise: an investigation by time-series analysis

Abstract: Meaningful dissociations between [Formula: see text]O2pulm and [Formula: see text]O2musc kinetics exist for both UpBody and LoBody exercise during rapid work rate changes. Therefore, isolated [Formula: see text]O2pulm kinetic estimations without the consideration of the circulatory distortions may not allow a reliable assessment of [Formula: see text]O2musc kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
2
11
2
Order By: Relevance
“…There are a number of possible explanations for the higher peak _ VO 2 values in TM exercise, including the energy cost of maintaining an upright posture (Miles-Chan et al, 2013;J udice et al, 2016) and/or factors related to work efficiency, skeletal muscle mass, and activation that occur in TM but not CE CPET. Muscle mass clearly plays a role; for example, peak _ VO 2 is, as expected, smaller in upper body ergometry compared with TM or CE CPET (Drescher et al, 2015). It is noteworthy that we could not find significant changes in any of our submaximal slopes in the transition from walking to running on the treadmill, suggesting that the predominant component of energy costs of TM exercise is related to velocity, mass, and incline.…”
Section: Lean Body Mass (Kg)supporting
confidence: 67%
“…There are a number of possible explanations for the higher peak _ VO 2 values in TM exercise, including the energy cost of maintaining an upright posture (Miles-Chan et al, 2013;J udice et al, 2016) and/or factors related to work efficiency, skeletal muscle mass, and activation that occur in TM but not CE CPET. Muscle mass clearly plays a role; for example, peak _ VO 2 is, as expected, smaller in upper body ergometry compared with TM or CE CPET (Drescher et al, 2015). It is noteworthy that we could not find significant changes in any of our submaximal slopes in the transition from walking to running on the treadmill, suggesting that the predominant component of energy costs of TM exercise is related to velocity, mass, and incline.…”
Section: Lean Body Mass (Kg)supporting
confidence: 67%
“…The kinetics of HR, V O 2 musc and V O 2 pulm of the aged subjects in this study were slower compared with recently published data using the same protocol in young subjects [19,27]. These findings are in line with the results of former studies comparing old and young subjects [2-4, 17, 18, 41, 42].…”
Section: Comparison Of Hr V O 2 Musc and V O 2 Pulm Kineticssupporting
confidence: 90%
“…The distortion is caused by the transport of the 'oxygen uptake signal' through venous volume, O 2 stores and the V O 2 of the non-working parts of the body e. g., [9,27], as similarly outlined by Barstow et al [7]. In young subjects it was shown that V O 2 musc kinetics were different from V O 2 pulm kinetics [19,27]. No data of V O 2 musc for elderly subjects evaluated via PRBS protocols are available, although the protocol has been tested in children with cystic fibrosis [33].…”
Section: Abstract ▼mentioning
confidence: 97%
See 1 more Smart Citation
“…For the T2D c group, V'O 2 musc kinetics seemed slower than HR kinetics. For comparison, HR kinetics have been shown to be faster than V'O 2 musc kinetics in healthy young subjects [14,28]. In sedentary aged subjects, V'O 2 musc kinetics were faster (but not significantly) than HR kinetics [29].…”
Section: Discussionmentioning
confidence: 99%